International community service: SULAM (UiTM) and SANGGAR BELAJAR (UNIJA) - community empowerment with science, Technology, Engineering & Mathematics (STEM) for Indonesian children in Malaysia - Abu Talib, Iffah Farhana; Mohd Nordin, Rumaizah; Brahim, Juliana; Anekawati, Anik (Universiti Teknologi MARA, Kedah, 2024)
Marginalized students often face significant barriers in accessing quality STEM education due to socioeconomic disparities and a lack of adequate resources. This educational gap deprives them of essential skills and opportunities, perpetuating cycles of poverty and limiting their potential for socio-economic mobility. Conducted in collaboration between Universiti Teknologi MARA (UiTM) and Universitas Wiraraja (UNIJA), with the support Indonesian Embassy, this initiative provides a unique platform for undergraduate students to engage with marginalized communities. The objective is to enhance public awareness and disseminate STEM knowledge among Indonesian children living in Shah Alam, Selangor, Malaysia, who are often excluded from formal education due to socio-economic and legal barriers. The project methodology involves a comprehensive community-based engagement approach. This includes content development, co-creation with local community leaders, interactive webinars, and hands-on activities designed to inspire and educate. The direct involvement of students in planning and execution allows them to apply theoretical knowledge in real-world settings, fostering their professional and personal growth. The outcomes of this initiative are manifold: increasing STEM literacy, empowering children with the skills to improve their circumstances, and fostering a spirit of civic engagement among university students. By aligning with Sustainable Development Goals (SDGs) 4 (Quality Education), 1 (No Poverty), and 10 (Reduced Inequalities), this project highlights the transformative power of education and international cooperation. It provides a replicable model for other institutions aiming to reduce educational inequalities and foster sustainable, inclusive development.